Discrete elemental parameter calibration of the bonding model for caking compound fertilizer utilized in oilseed rape mechanized direct seeding - Xiao, Wenli; Liao, Qingxi; Liao, Qingxi; Liao, Yitao; Wang, Lei; Wan, Xingyu (International Journal of Agricultural and Biological Engineering, 2025)
To address the problem that granular compound fertilizer is prone to agglomeration during mechanized direct seeding of oilseed rape in the middle and lower reaches of the Yangtze River, which causes clogging of the fertilizer discharger and leads to a reduction in the uniformity and stability of fertilizer discharge, research on the crushing mechanism of caking compound fertilizer was performed. Considering that it is difficult to measure the bonding force between caking fertilizer particles directly, a simulation model of caking composite fertilizer was established with the bonding model in EDEM discrete element software. To decrease error between the simulation and physical test results, the normal contact stiffness, tangential contact stiffness, critical normal stress, critical tangential stress, bonding radius, and other parameters of the bonding model of caking composite fertilizer were calibrated. The three-dimensional structure of the caking composite fertilizer was obtained via three-dimensional scanning, the critical crushing displacement and critical crushing force of the caking composite fertilizer were measured via compression testing with a mass spectrometer, and the optimal parameter combination of the bonding model was determined via EDEM discrete element simulation of the Plackett-Burman test, steepest ascent test, and Box-Behnken test. The results of the simulated compression tests under the optimal parameter combination show that the relative errors of the critical crushing displacement and critical crushing force with respect to the physical test results were 0.296% and 0.343%, respectively. Using the crushing rate of caking compound fertilizer as an evaluation index, the feasibility of the calibrated parameters was verified for a four-head spiral two-row fertilizer discharger installed in a direct seeding machine for oilseed rape. The results show that the relative errors of the caking fertilizer crushing rates from the simulation relative to those of the bench and field tests were 5.81% and 5.06%, respectively, indicating that the calibration parameters of the discrete element model were accurate and could be used for parameter analysis of caking fertilizer with a discrete element model. These results can provide a reference for the structural optimization of fertilizer discharger crushing of caking fertilizer of direct seeding machine for oilseed rape. Keywords: caking compound fertilizer, bonding model, three-dimensional scanning, parameter calibration, discrete element method DOI: 10.25165/j.ijabe.20251804.9201 Citation: Xiao W L, Liao Q X, Liao Y T, Wang L, Wan X Y. Discrete elemental parameter calibration of the bonding model for caking compound fertilizer utilized in oilseed rape mechanized direct seeding. Int J Agric & Biol Eng, 2025; 18(4): 17–25.